Modernizing the North Korean system : objectives, method, and application - Wolf, Charles, Jr., 1924-2016 (RAND Corp., 2008)
"In seeking a modernized North Korea, the focus should be on stimulating a gradual modernization of the North Korean system rather than removing the regime. With this tenet in mind, six institutions in five countries that have key interests in North Korea's future undertook a collaborative effort to determine ways in which the North Korean system could move toward modernization over the medium to long term. This endeavor can be viewed as "participatory systems analysis" in that the participants, in analyzing the North Korean system and how to motivate its modernization, fused their sometimes divergent but often overlapping and reconcilable perspectives on that system. The project first produced policy instruments that can contribute to the system's modernization and provide a basis for concerted, collaborative efforts to stimulate peaceful change in North Korea. These instruments were then integrated into alternative operational plans, or "portfolios," and evaluated in terms of how each member of the Six-Party Talks would respond to their components, spawning one "consensus plan" that all of the research partners deemed likely to garner buy-in from their five countries. In addition, several potential intermediaries -- i.e., those that could help convey the project findings to one or more levels of the North Korean structure -- were identified. The results of this project consist of illustrative plans, the consensus plan, and a tool kit that can be used by entities in North Korea or elsewhere to construct plans for stimulating modernization of the North Korean system."--Publisher's website